Tourism Management - Stephen J. Page (New York Routledge, 2019)
One of the leading texts in the field, Tourism Management is the ideal introduction to the fundamentals of tourism as you study for a degree, diploma or single module in the subject with a global focus.
Keywords: Travel; Tourism; (ETB-2001) A Sense of Place; (ETB-1001) Introduction to Travel Tourism Industry of Uzbekistan